Process and terminations variations aware stability criteria for microwave amplifiers. Issue 6 (26th November 2012) - Scotti, Giuseppe; Tommasino, Pasquale; Trifiletti, Alessandro
<x xml:space="preserve">Abstract</x> Two novel process variations aware, necessary and sufficient conditions suitable for implementation in CAD optimizers are proposed to check amplifiers stability. Case studies are presented, showing that the new criteria allow robust amplifier design, under variation of active device immittance parameters in pre‐specified rectangular regions, due to manufacturing tolerances. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE 23: 619–626, 2013.